Core-Shell-Like Structured Co3O4@SiO2 Catalyst for Highly Efficient Catalytic Elimination of Ozone - Ding, Jingya; Cheng, Feng; Meng, Zhen; Cao, Yan; Han, Fennv; Chen, Dongbin; Cao, Mingxiang; Zhang, Guolin; Kang, Jiahao; Xu, Shuxiang; Xu, Qi (Frontiers in Chemistry, 2021)
Co3O4 is an environmental catalyst that can effectively decompose ozone, but is strongly affected by water vapor. In this study, Co3O4@SiO2 catalysts with a core-shell-like structure were synthesized following the hydrothermal method. At 60% relative humidity and a space velocity of 720,000 h-1, the prepared Co3O4@SiO2 obtained 95% ozone decomposition for 40 ppm ozone after 6 h, which far outperformed that of the 25%Co3O4/SiO2 catalysts (40%). The superiority of Co3O4@SiO2 is ascribed to its core@shell structure, in which Co3O4 is wrapped inside the SiO2 shell structure to avoid air exposure. This research provides important guidance for the high humidity resistance of catalysts for ozone decomposition.